Maternal Self-Reported Genital Tract Infections During Pregnancy and the Risk of Selected Birth Defects - Carter, Tonia C. (Birth Defects Res A Clin Mol Teratol, 2010)
BACKGROUND: Genital tract infections are common during pregnancy and can result in adverse outcomes including preterm birth and neonatal infection. This hypothesis-generating study examined whether these infections are associated with selected birth defects. METHODS: We conducted a case-control study of 5913 children identified as controls and 12,158 cases with birth defects from the National Birth Defects Prevention Study (1997–2004). Maternal interviews provided data on genital tract infections that occurred from one month before pregnancy through the end of the first trimester. Infections were either grouped together as a single overall exposure or were considered as a subgroup that included chlamydia/gonorrhea/pelvic inflammatory disease. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using unconditional logistic regression with adjustment for potential confounders. RESULTS: Genital tract infections were associated with bilateral renal agenesis/hypoplasia (OR, 2.89; 95% CI, 1.11–7.50), cleft lip with or without cleft palate (OR, 1.46; 95% CI, 1.03–2.06), and transverse limb deficiency (OR, 1.84; 95% CI, 1.04–3.26). Chlamydia/gonorrhea/pelvic inflammatory disease was associated with cleft lip only (OR, 2.81; 95% CI, 1.39–5.69). These findings were not statistically significant after adjustment for multiple comparisons. CONCLUSIONS: Caution is needed in interpreting these findings due to the possible misclassification of infection, the limited sample size that constrained consideration of the effects of treatment, and the possibility of chance associations. Although these data do not provide strong evidence for an association between genital tract infections and birth defects, additional research on the possible effects of these relatively common infections is needed.